Latitudinal Variation in the Molecular Diversity and Community Composition of Symbiodiniaceae in Coral From the South China Sea - Chen, Biao; Yu, Kefu; Liang, Jiayuan; Huang, Wen; Wang, Guanghua; Su, Hongfei; Qin, Zhenjun; Huang, Xueyong; Pan, Ziliang; Luo, Wenwen; Luo, Yanqiu; Wang, Yinghui (Frontiers in Microbiology, 2019)
Coral reefs are continuing to decline worldwide due to anthropogenic climate change. The study of the molecular diversity and biogeographical patterns of Symbiodiniaceae, is essential to understand the adaptive potential and resilience of coral–algal symbiosis. Next generation sequencing was used to analyze the Symbiodiniaceae rDNA internal transcribed spacer 2 marker genes from 178 reef-building coral samples in eight coral habitats across approximately 13° of latitude in the South China Sea (SCS). A total of three Symbiodiniaceae genera, Cladocopium, Durusdinium, and Gerakladium, as well as 31 dominant Symbiodiniaceae types, were identified. Symbiodiniaceae richness, diversity, and community composition varied according to latitude; intermediate and low latitude coral reefs (IR and LR) have higher Symbiodiniaceae richness and diversity than high latitude coral habitats (HC and HR). A PERMANOVA analysis found significant differences in the Symbiodiniaceae community composition in the SCS (F = 14.75, R2 = 0.20, p = 0.001 < 0.01). The major dominant Symbiodiniaceae types were C1 in the HC and the HR, C1/Cspc/C50/C15 and D1 in the IR, and C3u and C15 in the LR. Canonical correspondence analysis showed that the relative abundance of different Symbiodiniaceae types is affected by multiple environmental factors. Phylogenetic analysis indicated that the Symbiodiniaceae type Cladocopium, which shared common ancestors, shows similar environmental adaptability. Based on these results, we suggest that coral host species played a relatively small role in the identity of the dominant Symbiodiniaceae type. Therefore, the biogeographical patterns of Symbiodiniaceae may be mainly affected by environmental factors. Our research provides a comprehensive overview of the biogeography of Symbiodiniaceae in the SCS, where coral communities and reefs are widely distributed across different latitude regions and have variable environmental conditions. Our data will provide support for further study of the regional diversification of Symbiodiniaceae and the ecological resilience of the coral-Symbiodiniaceae symbioses.